The Pacific. - Freeman, Donald B. (Seas in history., 2013)
"In this fascinating and exciting overview, Donald B. Freeman explores the role of the Pacific Ocean in human history. Covering over one third of the globe, the Pacific Ocean plays a vital role in the lives and fortunes of more than two billion people who live on its rim-lands and islands. It has played a crucial part in shaping the histories of the different Pacific cultures, towards which it has appeared in a variety of different guises. Exploring the ocean's place in human history, this wide ranging book draws together the long and varied physical, economic, cultural and political history of the Pacific, from Prehistory through to the present day. It takes an interdisciplinary approach to show the changing viewpoints of those who explored, exploited and settled the Pacific, including the inhabitants of its Asian and American rim-lands. The book draws on new research in a variety of areas, such as early Pacific migrations, impacts of European colonization, the effects of climate change, and current economic and political developments. It provides a uniquely broad overview that will be of vital interest to students and to all those with an interest in World History." --